A Comparison of Halal Product Standards in Indonesia and the Kingdom of Saudi Arabia - Khoiriah, Ulfah Lailatul; Prasiefa, Mizanurafi’ Ghifarhadi; Gunawan, Gunawan; Gunawan, Setiyo (Halal Research, 2024)
In the era of globalization and increasingly fierce economic competition, halal industry opportunities are an important focus of the government in understanding the dynamics of  the global market. The rapid growth of the Muslim market is partly due to the high birth rate  of Muslims compared to the birth rate in Western countries. This high growth has the potential to drive an increase in the market as well as the global economy because Muslims generally seek Halal products that are made following Islamic principles. The government continues to strive to develop this industry and make various regulations to regulate the entire process that occurs. Halal standards that apply in each country are, of course, different, and tailored to the conditions and needs of the country. The main purpose of this research is to analyze and compare the practice and regulation of halal products in Indonesia and Saudi Arabia. Based on comparative and qualitative analysis, it can be concluded that halal policies in Indonesia and Saudi Arabia have several significant differences, such as halal policies, procedures and provisions in halal certification, types of halal mandatory products, and slaughter criteria.